Organising community resilience: an examination of the forms of sociality promoted in community resilience programmes. Issue 1 (2nd January 2017) - Zebrowski, Chris; Sage, Daniel
Abstract: Communities have emerged as a principal strategic target for contemporary resilience programmes. Going beyond community preparedness campaigns, which aimed to responsibilise individual citizens to dangers, community resilience programmes aim to intervene in, and enhance, the social relations binding a community together in order to promote resilience. The benefits of resilience for communities, it is claimed, go beyond emergency preparedness and recovery; promising to enhance development, wellness and equality. This article examines the forms of sociality valued and promoted within the discourses and practices of community resilience programmes. We begin by examining how 'communities' emerged as a site for post-social forms of neoliberal governance. Next, we turn to examine the ideas of community, the forms of sociality and the modes of resilience enacted within community resilience programmes. We conclude with a discussion of how 'community resilience' could be enacted otherwise through a critical examination of alternative organisations.